Effect of distraction arthroplasty on osteoarthritic goat models of the articular cartilage (Faculty of Medicine Universitas Indonesia, 2013)
Background: Osteoarthritis (OA) is the most common knee degenerative disease, the number of OA patients increases along with the increase of life expectancy. Distraction arthroplasty is a less invasive alternatif for OA management by releaving mechanical stress while maintaining intermitten joint fluid pressure changes, thus halting the OA destructive cycle and inducing repair. This study aims to evaluate the anatomical and histopathological changes after distraction arthroplasty on osteoarthritic animal models. Methods: The study was performed on 32 goat stiffle joint (16 goats) with mechanically induced OA by lateral meniscectomy. During the study 6 goats were decreased. Distraction arthroplasty was performed using external fixation on 10 knees for 4 weeks, and the contralateral knees left untreated. The knees were anatomically and histopathologically examined using International Cartilage Repair Society (ICRS) staging and Osteoarthritis Research Society International (OARSI) scoring. The differences of the anatomical and histopathological changes are tested for significance using the Wilcoxon test. Results: There was anatomical and histopathological worsening of the OA on treated knees. The anatomical difference assessed using ICRS stage gave median values of 1.5 and 2.5 respectively (p < 0.002). The histopathological difference assessed using OARSI scoring was significant (6 vs 10; p < 0.002). Conclusion: Distraction arthroplasty in OA goat models in this study, worsens the OA instead of inducing repair. Further studies are required to find out a convincing biological basis of distraction arthroplasty as an alternative treatment for OA. (Med J Indones. 2013;22:64-9)